Implementation of School Literacy Movement in Cultivating Reading Interest of Grade IV Students of SD Negeri 36 Banda Aceh - Luthfi, Mahdiyah; Israwati, Israwati; Kurniawati, Rizki (Elementary Education Research, 2024)
Reading is an important activity in the development of knowledge. The quality of education is often associated with reading interest. Reading interest needs to be fostered from an early age. The School Literacy Movement is one of the government programs that seeks to foster students' reading interest through its activities. This study aims to determine the implementation of the School Literacy Movement (GLS) in establishing the reading interest of grade IV students of SD Negeri 36 Banda Aceh. The research approach used is a qualitative approach with a descriptive research type, and data collection techniques are observation and interview techniques. The results of this study indicate that the Implementation of the School Literacy Movement in fostering reading interest in grade IV students of SD Negeri 36 Banda Aceh is at the development stage and is considered successful in fostering reading interest in grade IV students. The school has made efforts that are carried out in stages to foster students' reading interest, namely through the stages of habituation, development, and learning. The habituation stage that has been implemented by SD Negeri 36 Banda Aceh is in the form of reading for 15 minutes before learning begins, visiting the library, providing a reading corner in the classroom, a reading garden, displaying literacy posters, students visiting the library, reading books in the reading corner, and recording the titles of books that have been read, and teachers motivating students after the activity. The development stage that has been implemented by SD Negeri 36 Banda Aceh is in the form of books available in the reading corner that vary, students are enthusiastic and motivated in carrying out reading activities, students carry out activities retelling the contents of the reading, and there is also a school literacy team that coordinates the implementation of the literacy program. The learning stage that has been implemented by SD Negeri 36 Banda Aceh is in the form of using enrichment books to accompany textbooks. In accordance with students' literacy abilities, carry out appropriate reading activities in the form of oral, written, art, handicrafts and other activities to be able to continue to foster students' interest in reading.